Faktor-faktor yang Mempengaruhi Penyerapan Tenaga Kerja Sektor Pariwisata di Kabupaten Banyuwangi - Rachman, Jalaluddin Abdul; Huda, Syamsul (Jurnal Riset Ilmu Ekonomi, 2025)
This study aims to analyze the effect of the number of tourists, the number of tourist objects, and the number of restaurants on employment in the tourism sector of Banyuwangi Regency. The research method uses regression analysis with secondary data sources in the form of time series data from 2014-2023 from the Central Bureau of Statistics. The results show that the increase in the number of tourists and the increase in tourist objects consistently encourage employment growth in this sector. In contrast, the number of restaurants does not show a strong relationship with the increase in employment, which is likely due to the adoption of digital technology and operational efficiency that reduces dependence on direct workers. This study contributes in providing relevant empirical evidence for local policy makers, particularly in designing tourism development strategies that are oriented towards sustainable and inclusive job creation.